A Patient with Recurrent Pyelonephritis and Renal Stones Associated with a Bochdaleks Hernia Involving the Proximal Ureter Treated by a Robot Assisted Approach and Retrograde Intrarenal Surgery: A Case Report - Ierides, Solon; Pautler, Stephen E.; Razvi, Hassan (Archives of Clinical and Medical Case Reports, 2026)
Background: Bochdalek hernia is a congenital posterolateral diaphragmatic defect that facilitates displacement of intra-abdominal organs into the thoracic cavity. It constitutes the most prevalent subtype of congenital diaphragmatic hernia with presentation in adulthood being uncommon and often incidental. Right-sided Bochdalek hernias occurs less frequently than left-sided lesions, and involvement of the ureter within the hernia sac is exceedingly rare. Case Presentation: We present a 68-year-old female patient with a history of recurrent urinary tract infections and right renal stones secondary to impaired drainage of her right kidney resulting from an abnormal course of her right proximal ureter into a Bochdalek’s hernia. Management of this case required appropriate imaging to confirm the diagnosis, and the application of minimally invasive endourology techniques for a successful outcome. Conclusion: This case highlights the importance of recognising unusual anatomical variations that can promote urinary stasis and to provide insight into minimally invasive surgical approaches to management.